Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1093/molbev/msac150
|View full text |Cite
|
Sign up to set email alerts
|

Sympatric Recombination in Zoonotic Cryptosporidium Leads to Emergence of Populations with Modified Host Preference

Abstract: Genetic recombination plays a critical role in the emergence of pathogens with phenotypes such as drug resistance, virulence, and host adaptation. Here, we tested the hypothesis that recombination between sympatric ancestral populations leads to the emergence of divergent variants of the zoonotic parasite Cryptosporidium parvum with modified host ranges. Comparative genomic analyses of 101 isolates have identified seven subpopulations isolated by distance. They appear to be descendants of two ancestral populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 52 publications
4
30
0
Order By: Relevance
“…The large-scale topology was consistent with the orthologous genes-based phylogeny. Corroborating indications from previous studies (Corsi et al 2023; T. Wang et al 2022), we observed that the host species and gp60 subtypes were “scattered” along the tree, the latter indicative of limited predictive power for the deep phyletic relationships within C. parvum . However, a partial correlation with the geographical origin was found, as isolates sampled from the same region/country, from a single farm, or collected within a narrow temporal window, formed evident subclusters (e.g., all but one of the Finnish isolates formed a monophyletic clade).…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…The large-scale topology was consistent with the orthologous genes-based phylogeny. Corroborating indications from previous studies (Corsi et al 2023; T. Wang et al 2022), we observed that the host species and gp60 subtypes were “scattered” along the tree, the latter indicative of limited predictive power for the deep phyletic relationships within C. parvum . However, a partial correlation with the geographical origin was found, as isolates sampled from the same region/country, from a single farm, or collected within a narrow temporal window, formed evident subclusters (e.g., all but one of the Finnish isolates formed a monophyletic clade).…”
Section: Resultssupporting
confidence: 76%
“…Table S1 lists the information available for the 195 C. parvum isolates from humans and ruminants included in this study. The dataset comprised 123 isolates sequenced in the present study, 71 isolates from previous studies (Hadfield et al 2015; Troell et al 2016; Feng et al 2017; Corsi et al 2023; T. Wang et al 2022), and the recently assembled IOWA-ATCC genome (Baptista et al 2022), which was used as a reference genome.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations